Salix alexeii, a new name for the extant Salix elongata L.He & Z.X.Zhang (Salicaceae) - Kottaimuthu, Ramalingam (Phytotaxa, 2017)
Salix Linnaeus (1753: 1015) is the most speciose genus in the family Salicaceae and comprises about 450 species (Argus et al. 2010). The genus is widely distributed in temperate and boreal regions of the Northern Hemisphere and a few species also occur in the Southern Hemisphere (Heywood et al. 2006). China is the centre of diversity for the genus Salix with 279 species (Wang et al. 2015) of these 189 species are endemics (Fang et al. 1999, He et al. 2016).